2015
DOI: 10.1080/1045988x.2014.977213
|View full text |Cite
|
Sign up to set email alerts
|

Active Supervision, Precorrection, and Explicit Timing: A High School Case Study on Classroom Behavior

Abstract: One proactive approach to increasing student engagement in schools is implementing Positive Behavior Intervention and Support (PBIS) strategies. PBIS focuses on prevention and concentrates on quality-of-life issues that include improved academic achievement, enhanced social competence, and safe learning and teaching environments. This study is a replication of a study that investigated the combination of active supervision, precorrection, and explicit timing. The purpose of the study was to decrease student pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…Furthermore, the most effective method of prevention is to set students up to be successful, creating a momentum for continued positive behavior as a replacement for misbehavior (Scott, 2016). One of the teacher strategies associated with decreases in student misbehavior is the teacher's active supervision of the instructional environment (Haydon & Kroeger, 2016).…”
mentioning
confidence: 99%
“…Furthermore, the most effective method of prevention is to set students up to be successful, creating a momentum for continued positive behavior as a replacement for misbehavior (Scott, 2016). One of the teacher strategies associated with decreases in student misbehavior is the teacher's active supervision of the instructional environment (Haydon & Kroeger, 2016).…”
mentioning
confidence: 99%
“…The current review identified seven single-case Note. Due to fewer than three data points within a phase, the following A-B contrasts were dropped from aggregate WC-LRR calculations: De Pry and Sugai 2002and Haydon and Kroeger (2016). Abs = absolute coding; BC-SMD = between-case standardized mean difference (Hedges, Pustejovsky, & Shadish, 2012, 2013 design studies that (a) were experimental, (b) reported at least one student-level outcome, and (c) took place with student(s) in a K-12 traditional school setting.…”
Section: Discussionmentioning
confidence: 99%
“…Again, the Q-statistic was significant and I 2 was 90%, indicating that a moderator analysis may be necessary. Unfortunately, a moderator analysis could not be conducted because too Colvin, Sugai, Good, and Lee (1997) Meets standards with reservations Strong DePry and Sugai 2002Does not meet Haydon and Kroeger (2015) Does not meet Haydon, DeGreg, Maheady, and Hunter (2012) Does not meet Jeffrey (2005) aMeets standards without reservations Strong Johnson-Gros, Lyons, and Griffith (2008) Does not meet Lewis, Colvin, and Sugai (2000) Does not meet Lyons (2006) a,b Does not meet McClain (2008) aMeets standards with reservations No evidence Patterson (2000) a and Patterson and van der Mars (2008) Does not meet Schuldheisz and van der Mars (2001) Does not meet Scherer 2017Meets standards with reservations Moderate…”
Section: Dissertationmentioning
confidence: 99%
“…The use of active supervision as a Tier-1 support can benefit all students and can prevent behavioral challenges for those with and at risk for EBD (McIntosh & Goodman, 2016). For example, researchers noted a reduction in the following problematic or disruptive behaviors as a result of active supervision: pushing, shouting, and throwing objects (Haydon & Kroeger, 2015); office discipline referrals (ODRs) for tardiness (Johnson-Gros, Lyons, & Griffith, 2008); hands on others and threats (Lewis et al, 2000); physical aggression (Lyons, 2006); and noncompliance with playground rules (Scherer, 2017). However, whether active supervision can in fact be considered an evidence-based practice remains unclear.…”
mentioning
confidence: 99%